2022
DOI: 10.3390/cells11233767
|View full text |Cite
|
Sign up to set email alerts
|

Development of Dementia in Type 2 Diabetes Patients: Mechanisms of Insulin Resistance and Antidiabetic Drug Development

Abstract: Dementia is reported to be common in those with type 2 diabetes mellitus. Type 2 diabetes contributes to common molecular mechanisms and an underlying pathology with dementia. Brain cells becoming resistant to insulin leads to elevated blood glucose levels, impaired synaptic plasticity, microglial overactivation, mitochondrial dysfunction, neuronal apoptosis, nutrient deprivation, TAU (Tubulin-Associated Unit) phosphorylation, and cholinergic dysfunction. If insulin has neuroprotective properties, insulin resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…In conclusion, a high TyG index may be associated with higher risk of cognitive impartment and dementia in adult population. tension, and dyslipidemia, all of which have been linked to cognitive dysfunction [11,12]. Recent research has suggested that the triglyceride-glucose (TyG) index, a parameter which is derived from fasting blood glucose and triglyceride levels, serves as a reliable indicator of IR [13].…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, a high TyG index may be associated with higher risk of cognitive impartment and dementia in adult population. tension, and dyslipidemia, all of which have been linked to cognitive dysfunction [11,12]. Recent research has suggested that the triglyceride-glucose (TyG) index, a parameter which is derived from fasting blood glucose and triglyceride levels, serves as a reliable indicator of IR [13].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic disorders may exhibit potential bidirectional interactions, thus offering ample opportunities for drug repurposing. Notably, diabetes is concurrently associated with several diseases in a bidirectional manner, such as cardiovascular and cerebrovascular diseases 9 , behavioral disorders 10 , cancer 11 , and dementia 12 , with diabetes medication metformin being utilized to assist in treating these conditions [13][14][15] . The accumulation of metabolic disorder states may lead to organ system damage, a process akin to aging 16 , affecting systems such as the cardiovascular 17 , nervous 18 , and endocrine systems 19 , with more severe accumulations potentially leading to various cancers 20 .…”
Section: Introductionmentioning
confidence: 99%